PELAKSANAAN MEDIASI KONFLIK PERCERAIAN DI MAHKAMAH SYAR’IYAH ACEH DILIHAT DARI PELUANG DAN TANTANGAN - Syah Iskandar (SYARIAH: Journal of Islamic Law, 2022)
The increasing number of divorces in Aceh Province is a concern for all of us for family resilience. There are many factors that can trigger a divorce, but all of the settlement processes must be submitted to the Mahkamah Syar’iyah as the official institution that oversees it. In an effort to resolve divorce cases, there are several processes that must be carried out, one of which is mediation. From several searches by researchers, the mediation efforts that have been carried out are still relatively ineffective. Therefore this study aims to further examine the implementation of divorce conflict mediation at the Mahkamah Syar’iyah Aceh and to see what are the opportunities and challenges of carrying out this mediation. This research is a library research with qualitative descriptive techniques. Data collection techniques are carried out through content analysis techniques. The results of the research will be presented in the form of a descriptive narrative in an easy-to-understand form. The results of this study indicate that there are still many challenges in conducting divorce mediation at the Mahkamah Syar’iyah Aceh. Besides that, there are also opportunities that can be optimized for the success of divorce mediation at the Mahkamah Syar’iyah Aceh.